Increased platelet procoagulant potential predicts recurrent stroke and TIA after lacunar infarction. (16th January 2020) - Kirkpatrick, Angelia C.; Vincent, Andrea S.; Dale, George L.; Prodan, Calin I.
Abstract: Background: Mean levels of coated‐platelets, a subset of highly procoagulant platelets, are decreased in patients with lacunar as compared to those with non‐lacunar stroke. Elevated coated‐platelets are associated with increased risk for recurrent infarction in non‐lacunar stroke and predict incident stroke after transient ischemic attack (TIA). Objective: We investigated if coated‐platelet levels are predictive of recurrent cerebral ischemia following lacunar stroke. Methods: Coated‐platelet levels were assayed in consecutive patients with acute lacunar stroke, who were followed for up to 12 months. Cox proportional hazards regression analysis was used to estimate the combined risk of stroke and TIA at 12 months according to initial coated‐platelet levels. Results: We enrolled a total of 109 lacunar stroke patients. Eight events were recorded over a mean follow‐up period of 10.8 months. A cut‐off of 42.6% for coated‐platelet levels yielded a sensitivity of 0.75 (0.35‐0.97; 95% confidence interval [CI]), specificity of 0.92 (0.85‐0.97), positive predictive value of 0.43 (0.26‐0.62), and a negative predictive value of 0.98 (0.93‐0.99) for recurrent stroke/TIA. The adjusted hazard ratio for recurrent stroke/TIA in patients with coated‐platelet levels ≥ 42.6% was 23.9 (95% CI: 4.26‐134.4) when compared to those with levels < 42.6%. Conclusions: Identification of increased platelet procoagulant potential may improve our ability to identify patients at higher risk of recurrent stroke/TIA following a lacunar stroke. Further study of mechanisms involved is warranted and may yield novel targets for prevention and treatment.